DISSOLVED OXYGEN CONCENTRATION CONTROLLER - KOBAYASHI SHUICHIRO; KUNIMI MASAKI; HONDA KAZUHIRO (1989)
PURPOSE:To improve energy efficiency by providing a DO control section which detects the DO value in an aeration tank and controls an aeration rate and a DO value monitor section. CONSTITUTION:A DO detector 4 is provided in the aeration tank 1 and the dissolved oxygen concn. value (DO value) in the aeration tank 1 is detected by the same. An air suction section 5 is provided in the tank 1 in order to control the DO value and the aeration air flow sucked form the air suction section 5 is controlled by controlling the value opening degree of an aeration air flow control valve 7 driven by an air flow control section 6. The dissolved oxygen concn. controller 12 has a process input/output section 13, a rate computing section 14, the DO value monitor section 15, a statistic processing section 16, and an energy saving rate pattern selecting section 17. The DO value X detected by the DO detector 4 is monitored and the aeration air flow is controlled. The saving of energy is attained in this way.